Improving English Language Ability of Children Aged 4-5 Years Old by Using Creative Dance - Sabila Nur Masturah; Myrnawati Crie Handini; Sofia Hartati; Elindra Yetti (JETL (Journal of Education, Teaching and Learning), 2018)
The aim of this research is to know about how to improve English language ability of children aged 4-5 years old by using creative dance. The subjects of this research were seven children in group A at Bilingual Kindergarten Rumah Pelangi Pondok Bambu, East Jakarta. This research was held during April-June, 2016. The method used is classroom action research proposed by Kemmis and Taggart in two cycles. Each cycle consists of planning, acting, observing, and reflecting. The children’s English language ability was still low. The presentation of success dealt between the researcher and collaborator was 71%. The result of data analysis of pre-research was 42,1%. After being given the action, the percentage increased to 61,87%. The data got from the first cycle has not achieved its target, so the researcher conducted the second cycle. The result was 80,41%. Based on the result in the second cycle, the hypothesis is proved. Qualitatively, it is also admitted that the children’s English language ability could improve their creative movement.source language using the incorrect grammatical, the sentence is vague, the idea is not coherent and many pungtuations.